DEVELOPMENT OF GUIDELINES FOR MICRO TEACHING IN EARLY CHILDREN EDUCATION FACULTY OF UNIVERSITAS MUHAMMADIYAH SURAKARTA - Darsinah Darsinah; Annisaa Salsabila; Sela Febriana (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2021)
The purpose of this study was to determine the need for Micro Teaching Guidelines for PG PAUD UMS (Universitas Muhammadiyah Surakarta) and produce Micro Teaching Guidelines for PG PAUD UMS according to the student needs. This research is a type of research and development or R D with ADDIE design. The subjects of this study were 6th semester students who were taking Micro Teaching courses. Data collection techniques were carried out using a google form questionnaire, and Forum Group Discussion. The data analysis technique uses percentage analysis and content analysis. Percentage analysis was carried out on data from google form, content analysis was carried out on data from discussion results. The results of this study indicate that: (1) 100% of respondents need a Micro Teaching Guidebook specifically for PG PAUD; (2) 100% of students and lecturers of PG PAUD UMS understand the contents of the Micro Teaching Guideline for PG PAUD UMS and stated that the Guidelines are effective for guide learning of Micro Teaching at PG PAUD UMS which seen from the criteria percentage of effectiveness.